TINJAUN YURIDIS PENGELOLAAN DAN PEMANFAATAN HASIL DENDA PELANGGARAN TERHADAP PENEGAKAN PERATURAN DAERAH KOTA PONTIANAK DALAM KONTRIBUSINYA BAGI PENINGKATAN PENDAPATAN ASLI DAERAH SESUAI DENGAN KEPUTUSAN MENTERI DALAM NEGERI NOMOR 7 TAHUN 2003 TENTANG PEDOMAN OPRASIONAL PENYIDIK PEGAWAI NEGERI SIPIL DAERAH DALAM PENEGAKAN PERATURAN DAERAH - NPM. A2021161072, DODHY ARYO YUDHO, SH (Jurnal NESTOR Magister Hukum, 2018)
ABSTRACTThis thesis discusses about juridical management and utilization of fines of violation against the enforcement of Pontianak City Regulation In Contribution To Increasing Original Income In accordance with Decree of Minister of Home Affairs Number 7 Year 2003 About Guidance of Oprasional Investigator of Regional Civil Servant in Enforcement of Local Regulation. The conclusion of this thesis that Pengelolahan and exploiting the result of fines violation from Enforcement of Local Regulation of Pontianak City, Pontianak City as one of governance in area need to arrange Local Regulation which arrange retribution of public service, even in the implementation have arranged in Local Regulation Number 4 Year 2011 about Retribution General Services. However, the existing regional regulations need to be adapted to the prevailing conditions of society and legislation as well as the management and utilization of the fines of violations of the enforcement of municipal regulations in the city of Pontianak in its contribution to the increase of indigenous revenues in accordance with Decree of the Minister of Home Affairs Number 7 of 2003 on Oprasional Guidelines Investigator of Regional Civil Servant in Enforcement of Local Regulation and Regional Finance Board of Pontianak City has the main duty